'It's an epidemic out there': Constructing the Online Solicitation of Children as a Social Problem - Cotter, Adam (Université d'Ottawa / University of Ottawa, 2012)
Social problems emerge when a behaviour, individual, or group is collectively defined as problematic. Online child solicitation is explored as a behaviour that has been defined as a social problem. This paper analyzes and explores the claims and claimsmaking process of one advocacy group, Perverted Justice. Their use of rhetorical strategies designed to persuade are of particular importance. In addition, the definitions, examples, and estimates they use to construct the problem are explored. Perverted Justice constructs the Internet as an inherently dangerous space, asserts that all children are at risk, and that online solicitation is a significant social problem. Furthermore, law enforcement, parents, and advocacy groups cannot protect children. Criticisms are rendered illegitimate through the use of rhetorical strategies. The way in which Perverted Justice constructs online child solicitation and their role in solving this issue incorporates elements of neo-liberalism, neo-conservatism, and vigilantism, reflecting the wider regulatory framework.
Keywords: rhetoric